PROGRAM WWZ: WAVELET ANALYSIS OF ASTRONOMICAL SIGNALS WITH IRREGULARLY SPACED ARGUMENTS - Andronov, I. L.; Naumova, A. V. (Одеські астрономічні публікації, 2013)
A program WWZ is introduced, which realizes the wavelet analysis using an improved modification of the algorithm of the Morlet wavelet for a general case of irregularly spaced data, which is typical for the databases available in virtual observatories. Contrary to the well-known analogs, working with regularly spaced (equidistant in time) arguments, we have implemented an improved algorithm presented by Andronov, (1998KFNT...14..490A, ..conf...57A), which significantly increases the signal-to-noise ratio. The program has been used to study semiregular pulsating variable stars (U Del et al.), but can be used the analysis of signals of any nature.